Negara Hukum Pancasila Dalam Konsepsi Prismatik - Divani Khaira Anggistya; Alisya Afifah Maulidina Putri Abdillah (Jurnal Hukum dan Sosial Politik, 2023)
The Pancasila Law of Indonesia is a unique and distinct legal concept for the Indonesian nation. The Pancasila Law is the result of Indonesia's long struggle for independence from colonization and the building of a free, democratic, sovereign, just, and prosperous nation. The Pancasila Law is not only based on constitutional documents or laws, but also has a strong philosophical and moral foundation that originates from Pancasila as the foundation of the Indonesian state. The concept of Pancasila Law in the three-dimensional prism, also known as the three aspects of trias politica, consists of functions, structure, and system. These three aspects are interconnected and cannot be separated from each other in carrying out their tasks and functions as the basis of the state law. Thus, the conclusion of the concept of Pancasila law is that it is a unique, complex, and holistic legal system that encompasses the values and principles of Pancasila as the foundation of the Indonesian state. Pancasila law combines legal, philosophical, and moral aspects while accommodating the cultural and religious diversity of Indonesia, and encourages societal participation in policy-making. Pancasila law is the result of the long struggle of the Indonesian people for independence and the building of a sovereign, democratic, just, and prosperous nation.